The Role of International Law in the Protection of Cultural Heritage in Armed Conflicts: The Case Study of Karabakh - Bagirova, Esmina; Mammadov, Tural; Davudlu, Ibrahim (ADA University, 2024)
The 1954 Hague Convention and other UNESCO Conventions form the international legal framework for the protection of cultural heritage during armed conflicts. However, the ineffectiveness of these Conventions was revealed during the Karabakh war and subsequent 30- year Armenian occupation when Azerbaijani cultural heritage in Karabakh was systematically destroyed. The question that this capstone project poses is why the legal framework failed to fulfil its objective. This paper identifies three main causes that hinder the effectiveness of the international law in the protection of cultural heritage during armed conflict such as legal gaps in 1954 Hague and Convention and UNESCO Conventions, legal gaps in safeguarding intangible cultural heritage, and bias of the international community towards Azerbaijan and the protection of its cultural heritage. The solutions proposed for each problem are taking legal actions to fill in the gaps on protection of cultural heritage in armed conflicts existing in Hague and UNESCO Conventions, conducting in-depth research on the IDPs of Karabakh for identification and protection of a unique intangible cultural heritage of Karabakh, and a submission of a complaint against Armenia to the International Court of Justice (ICJ) with regards to protection of Azerbaijani cultural heritage in Karabakh. Each of these solutions were evaluated using five criteria of effectiveness, efficiency, equity, feasibility and flexibility. This research heavily relies on primary data collected from the interviews with experts and secondary data obtained from books, journal articles, and websites of international and governmental agencies. This study comes to the conclusion that the government of Azerbaijan, primarily the Ministry of Culture with the support of other relevant Ministries and agencies, should work on the proposals for the improvement of the legal framework for the protection of cultural heritage during armed conflicts and present them to the international community.
Keywords: Cultural property -- Protection -- Law and legislation.; Cultural property -- Protection -- Azerbaijan.; Cultural heritage -- Protection -- Azerbaijan.; War damage to cultural property -- Azerbaijan.